Elisha’s dream for fast track PhD fuels her to strive for the Dean’s List Award every semester - Shalfarina, Shahriman (UMPSA, 2024)
GAMBANG, 21 October 2023 - The dream to continue her study to the Doctor of Philosophy (PhD) level through the fast-track route was finally achieved when she met the criteria set by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).